Adição de pó de aciaria como fonte de micronutrientes e diferentes níveis de calagem em solos de cerrados cultivados - Alves Filho, Anibal Sebastião (2010)
The savannas reached prominence in the development of corn (Zea mays L.), soybean (Glycine max L.) and processing tomato (Lycopersicum esculentum Mill.), Depending on the economic and social importance of these crops. The problems of acid soils and nutrient deficiency in the savannas are common in most soils, but once overcome these obstacles, the cultures exhibit satisfactory development and production. Increasingly it becomes necessary, by the dynamism that modern agriculture provides that alternative mechanisms of replenishment of nutrients to the soil are offered, due to the high cost of fertilizer and high extraction of these elements in each cycle of crops. The use of industrial waste from various sources has shown potential for agricultural use, for purposes of correction of acidosis, addition of macro and micronutrients to the soil or even physical conditioning of the soil, always under careful criteria used to avoiding the environmental contamination. The aim of this study was to evaluate the effect of the electric arc furnace dust coming from the steel industry as a source of micronutrients in crops of corn, soybean and tomato at different levels of liming. The tests were conducted in two locations. A field experiment was conducted at the experimental farm of the School of Agronomy and Food Engineering, Universidade Federal de Goiás, Campus Samambaia, in Goiânia-GO, Brazil and other, in a greenhouse at Palmital Farm, municipality of Urutaí-GO, in campus of the Instituto Federal Goiano. During three years, were evaluated in Goiânia-GO, the use of steelmaking dust in corn in rotation with soybean and, in Urutaí-GO, for seven months, the tomato crop in succession with soybeans. The results in both experiments indicated that the levels of heavy metals detected in soil and leaves of the plants analyzed were below the limits considered toxic.